Identification of Single Nucleotide Polymorphism (SNP) in Early Exon 10 of Follicle Stimulating Hormone Receptor (FSHR) Gene in Pesisir Cattle - Tinda Afriani; Endang Purwati; James Hellyward; Jaswandi Jaswandi; Mangku Mundana; Anna Farhana; Adisti Rastosari (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
The purpose of this study was to identify genetic diversity in the early exon 10 of the FSHR gene or follicle stimulating hormone receptor in Pesisir cattle. The blood samples used were 70 blood samples from female Pesisir cattle aged 2-5 years which were obtained from BPTU-HPT Padang Mengatas, West Sumatera. The isolated DNA was then amplified using a pair of primers L and R with PCR technique which produced a fragment with a length of 847 bp. The services of 1st Base Singapore are used for sequencing the amplified product. The results of the research on the identification of the early exon 10 FSHR gene in Pesisir cattle were found that there were 5 SNPs at positions --53T>C, +17A>G, +650C>T, +706A>C and +707 ins>A in some introns 9 to exon 10 first part. The results showed that the genotypic frequency of the Pesisir cattle population was in Hardy-Weinberg imbalance and polymorphisms were found in the early exon 10 FSHR gene diversity.